Cyanidin-3-glucoside Alleviates 4-Hydroxyhexenal-Induced NLRP3 Inflammasome Activation via JNK-c-Jun/AP-1 Pathway in Human Retinal Pigment Epithelial Cells - Xiaolu Jin; Chengtao Wang; Wei Wu; Tingting Liu; Baoping Ji; Feng Zhou (Journal of Immunology Research)
Recently, the NLRP3 inflammasome activation in the eyes has been known to be associated with the pathogenesis of age-related macular degeneration. The aim of this study was to investigate the protective effects of cyanidin-3-glucoside (C3G), an important anthocyanin with great potential for preventing eye diseases, against 4-hydroxyhexenal- (HHE-) induced inflammatory damages in human retinal pigment epithelial cells, ARPE-19. We noticed that C3G pretreatment to the ARPE-19 cells rescued HHE-induced antiproliferative effects. Cell apoptosis ratio induced by HHE was also decreased by C3G, measured by flow cytometry. The activation of NLRP3 inflammasome induced by HHE was found with increases of caspase-1 activity, proinflammatory cytokine releases (IL-1β and IL-18), and NLRP3 inflammasome-related gene expressions (NLRP3, IL-1β, IL-18, and caspase-1). The C3G showed potent inhibitive effects on these NLRP3 inflammasome activation hallmarks induced by HHE. Moreover, we noticed that the C3G’s pretreatment leads to a delayed and a decreased JNK activation in HHE-challenged ARPE-19 cells. Finally, using a luciferase reporter gene assay system, we demonstrated that HHE-induced activation protein- (AP-) 1 transcription activity was abolished by C3G pretreatment in a dose-dependent manner. Taken together, these data showed that HHE leads to inflammatory damages to ARPE-19 cells while C3G has great protective effects, highlighting future potential applications of C3G against AMD-associated inflammation.